Response of Garlic (Allium sativum L.) Yield to Combined Biochar, Lime, and Inorganic-Fertilizer Rates in the Case of Gimbi District, Western Ethiopia - Solomon Abeba Kenea; Tolera Abera Goshu; Kinati Chimdessa (Advances in Agriculture)
Soil degradation due to acidity is a serious problem in western Ethiopia, which would lower soil productivity and crop production. Implementing integrated soil fertility management is the most efficient approach for enhancing agronomic efficacy and boosting crop output while addressing the issue of soil acidity. This experimental study aimed to investigate the effect of combined coffee husk biochar (CHB), soil test-based value lime (STV), and inorganic-fertilizer (NPSB-fertilizer) rates on the optimum yield of garlic in Gimbi district, western Ethiopia. The field experiment was conducted during the 2022 cropping season on two sites. The experiment comprised 14 treatments laid out in a randomized complete block design with three replicates. Application of integrated biochar, lime, and inorganic-fertilizer rates showed a highly significant impact (p <0.01) on the yield and yield components of garlic. The treatment unit with T11 ha−1 had the significantly highest total fresh biomass yield (TFBY) per plant for both Farm-1 (65.9 g) and Farm-2 (75.3 g). Bulb yield fresh weight per plant (BWp) was highest in treatments of T4 and T8 ha−1 in Farm-1 (27.7–28.1 g) and in treatments of T4 and T11 ha−1, in Farm-2 (31.4–31.6 g). Marketable bulb yield (MBY) was significantly highest in treatments; T4, T7, T8, and T11 ha−1 in Farm-1 (8.5–9.3 tons ha−1) and Farm-2 (10.1–10.5 tons ha−1). Therefore, by combining, the application of 10 tons of biochar (CHB) + 75% of lime (STV) + 75% of inorganic-fertilizer (NPSB-fertilizer) ha−1 in strongly acid soil, and 7.5 tons of CHB + 50% of STV + 50% of NPSB-fertilizer ha−1 rates in very strongly acid soil are recommended for garlic production in Gimbi district, western Ethiopia, and similar areas. In order to draw firm conclusions, future research on more sites is necessary because this study was logically limited to two sites.